EFEKKTIVITAS PEMBERIAN JUS BUAH ALPUKAT TERHADAP PENURUNAN KADAR KOLESTEROL DI DESA NGABENREJO GROBOGAN: Array - Purhadi Purhadi; Nurulstyawan Tri Purnanto; Sutrisno Sutrisno (Pratama Medika : Jurnal Kesehatan, 2022)
Behind currently patients with heart disease tend to have increased from year to year, and this is in line with the progress of globalization is increasingly modern era many people forget the importance of a healthy lifestyle and healthy food consumption so that not a few people have high cholesterol levels in the blood. Hypercholesterolemia is a condition in which high levels of cholesterol in the blood exceeds 200 mg/dl. Avocado fruit juice therapy is one of management that can be used to lower cholesterol levels in a person who had hypercholesterolemia. This study of was to determine the effectiveness of feeding avocado fruit juice to decrease cholesterol levels in the village Ngabenrejo district of Grobogan. Research design used in this study is quasi experiment with methods one group pretest posttest. The technique sampling used is non- probability sampling as many as 15 respondents. Based on test results conducted found cholesterol levels to prior administration of the avocado fruit juice obtained an average value of 210.07 mg/dl where as cholesterol levels after administration of avocado fruit juice obtained an average value of 195.27 mg / dl. Test results of data analysis using paired t test results obtained on the sig (2-tailed) values obtained significansi 0.000 (p-value <0.05). Based paired t test results concluded that giving avocado fruit juice is effective in lowering cholesterol levels in the village Ngabenrejo district of Grobogan